KI GA SUMANAI DALAM DUNIA KERJA - Tri Mulyani Wahyuningsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
Ki ga sumanai is one of ethics Bushido code that is believed by the Japanese as the key of successful progress in Japan in various fields. One spirit of Bushido Ki ga sumanai has made the Japanese people become workaholic and always want to work and continue working. The totality of the soul directed for their work. Work is considered as a devotion to the country, thus work is the first priority in their live. The purpose of this paper is to find out more about the ontological and axiological aspects of Ki ga sumanai. This paper used descriptive and qualitative methods. Ki ga sumanai is like two sides of the coin. One side brings enormous benefits to the progress of Japan, but the other side it makes workers struggle to karoushi , but this is considered normally for them and think it is part of devotion. Now there is a new awareness that all contributions should be rewarded compensation.